Challenges and Countermeasures of International Commercial Dispute Resolution in the Digital Age - Zhi Qi (Ukrainian Policymaker)
This study discusses the challenges and countermeasures of international commercial dispute resolution in the digital age. With the digitalization of international commercial activities, the efficiency, transparency and innovation of dispute resolution have been improved. As an alternative method of dispute resolution, the development of the Online Dispute Resolution (ODR) is closely related to the Internet. However, the rapidity of technological updates, the lag of international rules, and the digital divide also bring challenges. To address these challenges, it propose proposed to enhance technical capabilities, strengthen data security, develop online dispute resolution platforms, update procedures and physical rules, lower technical barriers and narrow the digital divide. The article stressed that in order to adapt to the development of the digital economy, the rules for international commercial dispute resolution must be updated in a timely manner to ensure that the dispute resolution mechanism can flexibly, efficiently and fairly handle new types of disputes. At the same time, the joint efforts of the international community are needed to build a more perfect environment for international commercial dispute resolution.